Calculation of the Radionuclide Concentrations in Samples of Condiments by Using Gamma Spectroscopy System - Yaseen, Qabas A. J.; Subhi, Auday T.; Hadi, Ala A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this work  is to evaluate concentrations of  natural and artificial radionuclide  in nine different samples of condiments from local markets.     The concentrations of 238 U , 232 Th ,40k  and 137Cs  were measured by using gamma spectroscopy with a high- purity germanium detector. The concentrations of 238 U, 232 Th ,40k  and 137Cs   were found to be in a range of  (21.4 - 91.13), (15.7 - 88.11) , (285.56 â€“ 1100) and (5.1 - 27.5) Bq.kg-1  respectively. These concentrations are not hazardous to public health and the activities are within the allowed  levels